La vision du passé nordique chez les historiographes scandinaves de la fin du Moyen Âge au début du XVIIe siècle - Maillefer, Jean-Marie (Presses universitaires de Rennes, 2019)
In sixteenth century Scandinavia, historical writing played a significant role in establishing national identities, especially in Sweden—a country which did not have a medieval historiographical legacy as did its neighbours Denmark (Gesta Danorum) and Norway (Heimskringla). With the restored independence of Sweden in the 1520s, the new Vasa dynasty used both symbols of Biblical and Gothic heritage, so as to be considered as the new kings of Israel in order to match the pretensions of the Danish sovereigns to reinstate the Union of Kalmar for their benefit. It is also at this moment that patterns appear that are bound to the future image of the classical North, such as the love of Nature and Freedom.